Experimental investigation of a novel multi-tank thermal energy storage system for solar-powered air conditioning. (August 2017) - Chen, Liang; Jin, Sumin; Bu, Guangfeng
Highlights: A novel multi-tank TES for solar-power air conditioning was proposed. An optimized control strategy of multi-tank TES was proposed. The number of tanks had little effect on duration time of IHIWT in multi-tank TES. Longer duration time of IHIWT was obtained after optimized control strategy was adopted. Abstract: The volume of hot storage tank in sensible thermal energy storage (STES), integrated with solar-powered air conditioning to mitigate the misalignment between supply and demand, is too big which results in great thermal inertia. In this paper, a novel multi-tank thermal energy storage (TES) system for solar-power air conditioning, with the advantages of quick temperature rising and outstanding ability to fit variable weather, was proposed to mitigate the contradictions between demand and supply. In order to investigate effect of the number of tanks (NT) on system response time (SRT), total energy grade of water in tanks and temperature variations in charging and discharging periods, a series of experiments of TESs with different number of tanks (total volume of tanks is constant) were conducted under the same solar radiation conditions. Results show that the energy grade of water in tanks is improved through dividing thermal energy storage system into several tanks with different priorities of charging and discharging, and SRT decreases by 6.95 h in four-tank TES, compared with one-tank TES. Furthermore, the duration time of ideal heating inlet water temperature (IHIWT) in entire operational period increases slowly with the number of tanks, because NT has opposite effects on duration time of IHIWT in charging and discharging periods. An optimized control strategy that tanks stored heat successively in charging period and released heat simultaneously in discharging period was proposed. It is notable that the duration time of IHIWT in four-tank TES increases 2.59 h, about 26.67%, after the optimized control strategy is adopted. Therefore, the optimized TES makes the single-effect absorption chiller run at a high COP over a long time without strong variations of COP, compared with other TESs.